ANALYSIS OF THE PROBLEM OF ASSERTIVE BEHAVIOR OF AN INDIVIDUAL - Chulkova, Kseniya (PSYCHOLOGICAL JOURNAL, 2018)
The idea of ​​asserivity, which is covered in the article, involves the formation in the person of a certain quality of behavior, through which it can have spontaneous reactions, a reasonable manifestation of emotions, the ability to directly talk about their desires and requirements, able to express their own point of view, is not afraid to deny, using arguments, to insist on his situation in situations where any argument turns out to be superfluous; have the tactics of satisfying fair demands and failing to respond to unacceptable aspirations in a way that does not violate the rights of other people. Assertive behavior is a harmonious combination of the properties of a personality of man, manifestation of his knowledge of the nature of man, skills and communication skills, ethically permissible in a particular situation, manifestation in the form of concrete actions of ideological position of positive orientation. Austerity is the ability to organize its behavior; the ability to formulate their desires and demands, to seek their satisfaction, to ‘hear’ different thoughts. The article considers the specificity and diversity of views on the nature of assertiveness. Theoretical analysis of essence and contents of аssertiveness as a particular feature of adaptation subject allows to define the structure of assertive behavior, that includes cognitive and content, affective, behavioral components. It is substantiated that the leading factor of the assertive personality is the adaptation potential. On the basis of the theoretical analysis of psychological literature, an innovative approach to the problem of forming assertive behavior of an individual’s proposed.